2020
DOI: 10.1097/inf.0000000000002626
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Symptom Duration and Viral Reduction in Outpatient Children With Respiratory Syncytial Virus Infection

Abstract: Background: We investigated the association between age, duration of clinical symptoms and viral shedding in outpatient children infected with respiratory syncytial virus (RSV) in Japan. Methods: Outpatients younger than 2 years of age, with suspected RSV infection between 2014 and 2018, were enrolled in the study. Following informed consent, nasal samples were collected at first and second clinic visits (with 0–9 days gap). RSV-A or -B infection and viral load were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Through our investigations, we reported several new genotypes of NA1, NA2, BA7, BA8, BA9, and BA10, and found that a newly reported genotype in Canada, ON1, was imported to Japan in 2013 [14,18,26]. In addition to molecular epidemiology, we reported that RSV seasonality in Japan moves from winter to summer [24] and another report on clinical virology showed that patient age contributes to symptom duration and viral reduction in outpatients [27]. This study was also conducted as a part of this investigation, and samples were collected from various prefectures in Japan through our own network.…”
Section: Introductionmentioning
confidence: 72%
“…Through our investigations, we reported several new genotypes of NA1, NA2, BA7, BA8, BA9, and BA10, and found that a newly reported genotype in Canada, ON1, was imported to Japan in 2013 [14,18,26]. In addition to molecular epidemiology, we reported that RSV seasonality in Japan moves from winter to summer [24] and another report on clinical virology showed that patient age contributes to symptom duration and viral reduction in outpatients [27]. This study was also conducted as a part of this investigation, and samples were collected from various prefectures in Japan through our own network.…”
Section: Introductionmentioning
confidence: 72%
“… 1 The infection occurs in all age groups, but most children are infected at or before 2 years of age. 2 Patients with HRSV bronchiolitis usually present with two to four days of upper respiratory tract symptoms such as fever, rhinorrhea, and congestion, followed by lower respiratory tract symptoms such as increasing cough, wheezing, and increased respiratory effort. 3 However, it is not clear whether lower respiratory tract infections (LRTI) caused by HRSV cause different clinical manifestations in children of different ages.…”
Section: Introductionmentioning
confidence: 99%
“…Viral load measurement provides valuable information regarding the replication kinetics of the virus, shedding patterns, and host immune responses, all of which can significantly affect disease outcomes and transmission potential. 7 , 8 Assessment of the viral load can provide valuable insights into the patterns and impact of RSV infection, contributing to the establishment of effective strategies for prevention, treatment, and control. Current treatment options are supportive; however, antiviral trials are ongoing and new preventive options are available.…”
Section: Introductionmentioning
confidence: 99%